Integration of Plant Responses to Environmentally Activated Phytohormonal Signals - Achard, P.; Cheng, H.; De Grauwe, L.; Decat, J.; Schoutteten, H.; Moritz, T.; Van Der Straeten, D.; Van Der Straeten, D.; Harberd, N.P.
Plants live in fixed locations and survive adversity by integrating growth responses to diverse environmental signals. Here, we show that the nuclear-localized growth-repressing DELLA proteins of Arabidopsis integrate responses to independent hormonal and environmental signals of adverse conditions. The growth restraint conferred by DELLA proteins is beneficial and promotes survival. We propose that DELLAs permit flexible and appropriate modulation of plant growth in response to changes in natural environments.